2007
DOI: 10.1016/j.eplepsyres.2006.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Temporal sequence of ictal discharges propagation in the corticolimbic basal ganglia system during amygdala kindled seizures in freely moving rats

Abstract: We used a multiple channel, single unit recording technique to investigate the neural activity in different corticolimbic and basal ganglia regions in freely moving rats before and during generalized amygdala kindled seizures. Neural activity was recorded simultaneously in the sensorimotor cortex (Ctx), hippocampus, amygdala, substantia nigra pars reticulata (SNr) and the subthalamic nucleus (STN). We observed massive synchronized activity among neurons of different brain regions during seizure episodes. Neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 75 publications
2
17
0
2
Order By: Relevance
“…Hippocampal unit activity has been recorded and analyzed in animal models of temporal lobe epilepsy while kindling (Shi et al 2007) and during latent (Sanchez et al 2006), interictal (Liu et al 2003), and postictal periods (Zhou et al 2007), but not during spontaneous seizures. In patients with temporal lobe epilepsy, unit recordings have been obtained from the mesial temporal lobe during spontaneous seizures (Babb and Crandall 1976;Babb et al 1987;Verzeano et al 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Hippocampal unit activity has been recorded and analyzed in animal models of temporal lobe epilepsy while kindling (Shi et al 2007) and during latent (Sanchez et al 2006), interictal (Liu et al 2003), and postictal periods (Zhou et al 2007), but not during spontaneous seizures. In patients with temporal lobe epilepsy, unit recordings have been obtained from the mesial temporal lobe during spontaneous seizures (Babb and Crandall 1976;Babb et al 1987;Verzeano et al 1971).…”
Section: Introductionmentioning
confidence: 99%
“…21) Massive synchronized firings were observed among neurons of sensorimotor cortex, hippocampus, amygdalae and subthalamic nucleus during seizure episodes. 22) It is well accepted that the hippocampus is critical in the formation of declarative memories. Interestingly, electrophysiological studies demonstrated that this region also has a particularly low seizure threshold, where globally synchronous synaptic activity occurred.…”
mentioning
confidence: 99%
“…In kindling induced seizures, the SNR controls the transition from limbic to generalized motor seizures. 30-32 In the SNR of adult male rats, infusions of GABA A receptor agonists in the SNR anterior and SNR posterior subregions mediate separate inhibitory or facilitatory effects respectively on the onset, propagation and/or termination of generalized seizures. 11,33 Veliskova et al 34 found that in the flurothyl-induced generalized seizures in rats, the SNR posterior subregion was selectively active during the pre-clonic period while the SNR anterior was not involved at this stage.…”
Section: Discussionmentioning
confidence: 99%